An integrative approach to developing sporting excellence. Insights from FC Barcelona`s `La Masia` - Rees, L. (ASPETAR Sports Medicine Journal, 2018)
`La Masia`, the FC Barcelona (FCB) youth academy, translates into English, simply as `the farmhouse`. The FCB motto is `més que un club1`, and as one of the most successful sporting teams in the world2 FCB is definitely more than a club, and La Masia is - without doubt - more than just a farmhouse.